PENGARUH OLAHRAGA ADAPTIF TERHADAP KEMAMPUAN FISIK DAN KEMANDIRIAN ANAK TUNAGRAHITA - sesilia, agneta grace; Muksin, Muksin; Agustin, Muhammad Nandi; Wijaya, Habibi Hadi; Kusumaningtyas, Avinda Rizki (LPPM UM Metro, 2025)
This study aims to analyze the development of gross motor skills, coordination, basic cognitive abilities, social interaction, and independence of students with moderate intellectual disability through the application of adaptive physical activities, specifically a ball throwing and catching game, conducted at SLB B-C Cahaya Bangsa Karawang. The study used a quantitative descriptive method involving five students aged 13–15 years and observations were carried out across two sessions. A four-level observational rubric was used to assess students’ basic abilities. The results indicate consistent improvements across all aspects with an average increase of 29 percent, where the highest improvements were seen in social interaction at 45 percent followed by gross motor skills at 38 percent. These findings demonstrate that simple repetitive adaptive physical activities can significantly stimulate the physical, cognitive, and social development of students with intellectual disabilities. This supports the concept that structured and enjoyable physical activities create a more responsive learning environment for children with special needs.